Levels of circulating GRP78 and CHOP in endoplasmic reticulum stress pathways in Chinese type 2 diabetic kidney disease patients. Issue 33 (20th August 2021) - Ma, Ning; Xu, Ning; Yin, Dong; Zheng, Ping; Liu, Weiwei; Wang, Guofeng; Hui, Yuan; Han, Guanjun; Yang, Chuanhui; Cheng, Xingbo
Abstract : Abstract: The current study aimed to investigate circulating glucose-regulated protein 78 (GRP78) as well as CCAAT/enhancer-binding protein homologous protein (CHOP) concentrations in Chinese type 2 diabetes mellitus (T2DM) patients, especially those with microalbuminuria. We recruited 67 patients with T2DM and 63 control subjects. We determined circulating GRP78 and CHOP concentrations by ELISA, collected anthropometric data, and measured biochemical parameters in a clinical laboratory. Compared with control groups, patients with T2DM showed decreased circulating levels of GRP78 (0.21 [0.16–0.24] vs 0.16 [0.16–0.19] ng/mL, P  < .01) and CHOP ([0.29 ± 0.02] vs [0.27 ± 0.03]ng/mL, P  < .01). Reduction in circulating GRP78 and CHOP levels was more pronounced in patients with more severe categories of albuminuria. Amounts of circulating GRP78 correlated directly with serum fasting c-peptide, cystatin-c (Cys-c), creatinine (Cr), blood urea nitrogen (BUN), and uric acid, and inversely with glomerular filtration rates. Circulating CHOP level was positively correlated with age, Cr, BUN, Cys-c, and urinary microalbumin/creatinine (UmALB/Cr). Circulating GRP78 was predicted independently by Cr, BUN, serum uric acid, estimated glomerular filtration rate, and Cys-c, while CHOP depended on age, Cr, BUN, estimated glomerular filtration rate, UmALB/Cr, and Cys-c. After controlling for confounding factors, circulating GRP78 and CHOP expression were significantly associated with diabetic kidney disease (binary logistic regression, P  < .01). Patients with T2DM showed increased circulating GRP78 and CHOP concentrations. Receiver operating characteristic areas under the curve for predicting diabetic kidney disease based on GRP78 and CHOP were 0.686 (95% CI: 0.558–0.813) and 0.670 (0.524–0.816), respectively.